Bloodstream infections caused by Acinetobacter species with reduced susceptibility to tigecycline: clinical features and risk factors. (September 2017) - Park, Ga Eun; Kang, Cheol-In; Cha, Min Kyeong; Cho, Sun Young; Seok, Hyeri; Lee, Ji Hye; Kim, Ji Yeon; Ha, Young Eun; Chung, Doo Ryeon; Peck, Kyong Ran; Lee, Nam Yong; Song, Jae-Hoon
Abstract: Introduction: During recent decades, the rates of multidrug resistance, including resistance to carbapenems, have increased dramatically among Acinetobacter species. Tigecycline has activity against multidrug-resistant Acinetobacter spp, including carbapenem-resistant isolates. However, reports of tigecycline-resistant Acinetobacter spp are emerging from different parts of the world. The purpose of this study was to evaluate potential risk factors associated with tigecycline non-susceptible Acinetobacter bacteremia. Methods: The medical records of 152 patients with Acinetobacter bacteremia attending Samsung Medical Center between January 2010 and December 2014 were reviewed. Non-susceptibility to tigecycline was defined as a minimum inhibitory concentration (MIC) of tigecycline ≥4 μg/ml. Cases were patients with tigecycline non-susceptible Acinetobacter bacteremia and controls were those with tigecycline-susceptible Acinetobacter bacteremia. Results: Of the 152 patients included in the study, 61 (40.1%) had tigecycline non-susceptible Acinetobacter bacteremia (case group). These patients were compared to 91 patients with tigecycline-susceptible Acinetobacter bacteremia (control group). The case group showed high resistance to other antibiotics (>90%) except colistin (6.6%) and minocycline (9.8%) when compared to the control group, which exhibited relatively low resistance to other antibiotics (<50%). Multivariate analysis showed that recent exposure to corticosteroids (minimum 20 mg per day for more than 5 days within 2 weeks) (adjusted odds ratio (OR) 2.887, 95% confidence interval (CI) 1.170–7.126) and carbapenems (within 2 weeks) (adjusted OR 4.437, 95% CI 1.970–9.991) were significantly associated with tigecycline non-susceptible Acinetobacter bacteremia. Although prior exposure to tigecycline was more common in the case group than in the control group (9.8%, 6/61 vs. 2.2%, 2/91; p = 0.046), this variable was found not to be a significant factor associated with tigecycline non-susceptibility after adjustment for other variables (adjusted OR 1.884, 95% CI 0.298–11.920; p = 0.501). Conclusions: These data suggest that tigecycline non-susceptible Acinetobacter spp have emerged and disseminated in the hospital in association with a recent exposure to carbapenems and an immunosuppressed state. This indicates that the rational use of antibiotics through a comprehensive antimicrobial stewardship program, especially in immunosuppressed patients, may be essential in limiting the emergence and spread of multidrug-resistant organisms such as tigecycline-resistant Acinetobacter spp, which are difficult to treat.